Entrepreneurial Education and Entrepreneurial Skills: Study of Higher Education Students in Indonesia - Bintoro Bagus Purmono (Yayasan Ilomata, 2023)
The nation's economy has grown as a result of entrepreneurial activity. Through innovative programs and a research-oriented culture, formal and informal educational institutions must play a significant role in cultivating an entrepreneurial spirit in Indonesian higher education students. The development of initial entrepreneurial competencies, which are then manifested in entrepreneurial activities, is primarily facilitated by educational institutions. This study will examine the extent to which Indonesian higher education students' entrepreneurial skills are influenced by entrepreneurial education. This research is important as part of the academic contribution the concentration on increasing the number of young entrepreneurs in Indonesia which needs to be continuously improved. This study will use a causal design approach with structural equation modeling (SEM) as a statistical approach to testing the constructed constructs and hypotheses. The number of samples used in this study were 225 respondents from business activists at Indonesian Higher Education Students. The study shows that Indonesian university students' entrepreneurial skills are significantly influenced by entrepreneurial education.